NOVEL COVID-19 DETECTION AND DIAGNOSIS SYSTEM USING IOT BASED SMART HELMET - Mohammed, M. N.; Syamsudin, Halim; Zubaidi, S. Al-; K, Sairah A.; Ramli, Rusyaizila; Yusuf, Eddy (International Journal of Psychosocial Rehabilitation, 2020)
Coronavirus is the new virus that has not been identified in humans before which it causes the coronavirus disease called COVID-19. This disease was firstly discovered in Wuhan, China, on December 2019 and spread to the world until now. The virus can easily pass from person to person which make it spreaded rapidly. One of the common symptom of COVID-19 that can be easily identified is fever. Since the virus outbreak, thermal screening using infrared thermometers are used at public places to check the body temperature to identify the indicated infectee among crowd. This prevention still lacking because it spends a lot of time to check the body temperature from every person and the most importance is the close contact of the infectee might lead to spreading it to the person who do the screening process or from the one in charge of screening to the checked people. This study proposes the design of system that has capability to detect the coronavirus automatically from the thermal image with less human interactions using smart helmet with Mounted Thermal Imaging System. The thermal camera technology is integrated to the smart helmet and combined with IoT technology for monitoring of the screening process to get the real time data. In addition, the proposed system is Equipped with the facial-recognition technology, it can also display the pedestrian’s personal information which can automatically take pedestrians’ temperatures. This proposed design has a high in demands from the healthcare system and can potentially help to prevent for coronavirus spreading wider.